Análisis comparativo del desarrollo de los sistemas bancarios del Perú y Chile - Cortez Cortez, Gaby (2013)
The degree of development and depth of Peru’s banking system is below the average for Latin America during the years 2006-2012, while the banks of Chile is above that average. In terms of concentration, Chilean banks are less concentrated than the banks of Peru, which would show the increased market power of the Peruvian banks. Generally the profitability of banks in Peru is higher than the banks in Chile. On the other hand, in terms of the credit structure Chilean banks differ primarily because in addition to finance companies, the credit to mortgage industry is second in importance, while in the case of Peruvian banks, the financial resources target at companies first and second to consumer credit.